Challenging the Algerian master narrative in Samir Toumi's L'Effacement (2016): a counter-narrative for a mujahidin haunting. Issue 5 (20th October 2018) - Orlando, Valérie K.
ABSTRACT: L'Effacement (2016), contemporary Algerian author Samir Toumi's second novel, is a first-person narrative by an unnamed 44-year old man. To the protagonist's horror his reflection in the mirror is slowly disappearing despite psychiatric treatments prescribed by 'Doctor B' who explains that the protagonist's malady is ' le syndrome de l'effacement … ' (the erasure syndrome). This syndrome seems to affect only men born after Algeria's 1962 independence from France. These men are unable to shake the presence of their mujahidin fathers who fought with the Front de Libération (FLN) against the French, forsaking their youth for the cause of freedom. This essay studies L'Effacement in the context of the contemporary sociopolitical landscape of today's Algeria. Now, almost 55 years after the Algerian revolution, Toumi asks readers to acknowledge that the FLN Mujahidin Fathers continue to impede Algeria's younger generations from forging a future liberated from the stifling remnants of a heavy past.